1979
DOI: 10.1128/iai.26.1.362-368.1979
|View full text |Cite
|
Sign up to set email alerts
|

Attachment pili from enterotoxigenic Escherichia coli pathogenic for humans

Abstract: Pili from enterotoxigenic Escherichia coli pathogenic for humans have been isolated by adsorption to the surface of erythrocytes followed by thermal elution. The pili are composed of two protein subunits with molecular weights of 13,100 and 12,500 as determined by sodium dodecyl sulfate-gel electrophoresis. These pili also bind to human buccal cells under temperature conditions (37 degrees C) which prevent the binding of these pili to the erythrocytes. Analogous temperature effects on binding have previously b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0

Year Published

1981
1981
1985
1985

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(18 citation statements)
references
References 37 publications
2
16
0
Order By: Relevance
“…All P fimbriae yielded two bands in the SDS-PAGE; one of the preparations (KS71) even yielded three bands. A similar multiple SDS-PAGE pattern of purified fimbrial preparations has recently been reported from an E. coli strain causing diarrhea (3), as well as from other strains (10). We do not consider the various bands to be nonfimbrial contaminants since different batches of purified fimbriae gave identical SDS-PAGE patterns.…”
Section: Discussionsupporting
confidence: 58%
“…All P fimbriae yielded two bands in the SDS-PAGE; one of the preparations (KS71) even yielded three bands. A similar multiple SDS-PAGE pattern of purified fimbrial preparations has recently been reported from an E. coli strain causing diarrhea (3), as well as from other strains (10). We do not consider the various bands to be nonfimbrial contaminants since different batches of purified fimbriae gave identical SDS-PAGE patterns.…”
Section: Discussionsupporting
confidence: 58%
“…Recently Deneke et al (6,7) have identified three distinct pilus serotypes found on ETEC strains. Antisera raised against these pili reacted with 56% of ETEC strains from humans.…”
Section: Discussionmentioning
confidence: 99%
“…The fractionation method described was a modification of the procedures described by Nowicki et al [19] and Deneke et al [22]. An S-fimbriated population was obtained by adding Saccharomyces cerevisiae cells [23] (final concentration 10% (v/v)) to 2 ml of bacterial culture (10 '1 cells/ml).…”
Section: Fractionation Of Cellsmentioning
confidence: 99%